Controllable superlubricity of glycerol solution via environment humidity - Chen, Zhe (Langmuir : the ACS journal of surfaces and colloids, 2013)
The effect of humidity on the lubrication property of glycerol solution between steel surfaces has been investigated in this paper. A stable superlubricity with a friction coefficient about 0.006 has been found under the relative humidity between around 40% RH and 50% RH. Especially, it is noted that the lubrication state can be switched between superlubricity and nonsuperlubricity by adjusting humidity, which is attributed to the humidity-dependent hydrogen-bonding pattern in the solution. The mechanism of such superlubricity is attributed to the hydrated layer of water between the surface layers, which is formed by hydrogen-bonded glycerol and water molecules and strong enough to bear load, absorbed on each side of the solid surfaces. The work has potential applications, providing a simple and environment-friendly way to accomplish controllable superlubrication between steel pairs, which are commonly used in industry